The symbol of a reflection for peace. (Journal of Parents and Teachers, 2014)
In September a project called Bilbao: Peace and Tolerance was held in Bilbao, which covered the city with multicolored pigeons, as this animal is the symbol of peace.
Keywords: Bilbao; peace; tolerance; pigeons.